2020
DOI: 10.7554/elife.62518
|View full text |Cite
|
Sign up to set email alerts
|

Structure of bacterial phospholipid transporter MlaFEDB with substrate bound

Abstract: In double-membraned bacteria, phospholipid transport across the cell envelope is critical to maintain the outer membrane barrier, which plays a key role in virulence and antibiotic resistance. An MCE transport system called Mla has been implicated in phospholipid trafficking and outer membrane integrity, and includes an ABC transporter, MlaFEDB. The transmembrane subunit, MlaE, has minimal sequence similarity to other transporters, and the structure of the entire inner-membrane MlaFEDB complex remains unknown.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 77 publications
7
64
0
Order By: Relevance
“…It should be emphasized that the structural studies reported here favour an anteretrograde direction for lipid transport by structure similarity, as supported by our previous biochemical data in A. baumannii 21 as well as other studies on E. coli 12 , 19 , 21 . Nonetheless, other assays point towards a retrograde directionality 20 , 23 , and the current structures do not conclusively preclude this.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It should be emphasized that the structural studies reported here favour an anteretrograde direction for lipid transport by structure similarity, as supported by our previous biochemical data in A. baumannii 21 as well as other studies on E. coli 12 , 19 , 21 . Nonetheless, other assays point towards a retrograde directionality 20 , 23 , and the current structures do not conclusively preclude this.…”
Section: Discussionsupporting
confidence: 90%
“…We also emphasize that the detergent binding pockets observed in our MlaBDEF ab structures are also confirmed in the MlaBDEF ec structures, notably the lipids found between the MlaD TM and the N-terminal helix of MlaE 19 , and the detergent present in the central cavity 19 21 . For the latter, different exact detergent positions are observed depending on the state and study, but they are largely consistent with the lipid positions we have obtained in the MD simulations, with the charged group buried at the MlaE–MlaD interface.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…3 ) and 3.05 Å (ref. 4 ), respectively, in the presence of a membrane scaffolding protein to produce lipid nanodiscs. These findings largely recapitulate the structure reported by Tang et al, which was solved at 3.3 Å resolution using a mixture of detergent and phospholipids.…”
Section: Russell E Bishopmentioning
confidence: 99%
“…First described by Waller in 1850 (hence also known as Wallerian degeneration) 1 , groundbreaking research over the past ten years has established that the protein SARM1 has a critical role in axon degeneration 2,3 and contributes to various neurological and neurodegenerative diseases (reviewed in refs. [4][5][6] ). SARM1 has nicotinamide adenine dinucleotide (NAD + ) hydrolase (NADase) activity, and its destruction of NAD + triggers axon degeneration 7,8 .…”
Section: Competing Interestsmentioning
confidence: 99%